Influence Of Cyp2d6 And Drd2 Polymorphisms On Clinical Outcomes Of Patients With Schizophrenia - Zahari, Zalina (2009)
CYP2D6 is a polymorphic enzyme involved in the metabolism of many centrally acting drugs as well as cardiovascular drugs. Dopamine D2 receptor gene (DRD2) is a candidate gene implicated in the etiology of schizophrenia and the efficacy of antipsychotic drugs. CYP2D6 and DRD2 polymorphisms have been associated with antipsychotic drug response in patients with schizophrenia. The objectives of this study were to develop PCR methods for detection of DRD2 polymorphisms and to investigate the association of the CYP2D6 and DRD2 polymorphisms with treatment outcomes in patients with schizophrenia. The protocol for the study was approved by the Research and Ethical Committee, Universiti Sains Malaysia (USM), Kelantan, Malaysia. The subjects were patients with schizophrenia (DSM-IV) on antipsychotic treatment or had been treated with antipsychotic in the past. Patients with co-morbid diagnoses of substance abuse or mental retardation were excluded from the study. Written informed consent was obtained from the subjects after full explanation of the study procedure. The selected patient was then called for interview and further assessment. The psychopathological severity was evaluated using the Positive and Negative Symptoms Scale (PANSS). The extrapyramidal side-effects and akathisia were assessed with the Simpson Angus Scale (SAS) and the Barnes Akathisia Rating Scale (BARS), respectively. DNA was extracted from blood taken from the patients using salting out procedures and subjected to PCR-genotyping. Specific primers were designed to develop PCR methods for detection of polymorphisms. The PCR methods were specific and sensitive to detect CYP2D6 and DRD2 genotypes. These methods were used for genotyping analysis of 156 subjects enrolled in this study for CYP2D6 and DRD2 polymorphisms. The frequencies for CYP2D6*1, *4, *5, *10 and CYP2D6 duplication were 39.1, 1.3, 3.8, 46.8 and 3.2%, respectively; while CYP2D6*3, *6, *9, *14 and *17 were absent. The frequencies for DRD2 variants Ser310, Cys311, TaqI A1, -141C Del and -241G were 0.3, 3.2, 42.3, 14.7 and 17.6%, respectively. There was no patient tested positive for Ala96, Leu141(T) and Ile154 variants. We found that CYP2D6 polymorphism was significantly associated with subtotal negative PANSS score. Patients with the Cys311 allele presented with significantly higher PANSS scores than those without the Cys311 allele. We also found that CYP2D6 and DRD2 polymorphisms were not related to the side-effects of antipsychotic therapy, and the SAS and BARS scores. However, A-241G polymorphism was associated with the experience of side-effects in the past two years. The results suggested that CYP2D6 and DRD2 polymorphisms may have implications in the treatment response and the occurrence of neuroleptic-induced side-effects. Therefore, CYP2D6 and DRD2 polymorphisms may be a predictor for the treatment outcomes of patients with schizophrenia. Further investigation is however required to confirm this using a larger sample.